1995
DOI: 10.1111/j.1365-294x.1995.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic structure of a natural population of Rhizobium leguminosarum bv. trifolii isolated from Trifolium subterraneum L.

Abstract: A collection of 121 isolates of Rhizobium leguminosarum biovar (bv.) trifolii was obtained from root nodules of Trifolium subterraneum L. (subclover) plants growing in an established pasture. The collection consisted of a single isolate from each of 18 plants sampled from seven microplots. The following year, a further 28 and 27 isolates were collected from the first and seventh sampling points, respectively. Analysis of restriction fragment length polymorphisms (RFLPs) of both chromosomal and Sym (symbiotic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
2
23
1
2
Order By: Relevance
“…It is therefore not surprising that our relatively short chromosomal probe detected a similar number of genetic groups per isolate sampled as was found in previous studies [8 genetic groups͞69 isolates sampled in this study compared with 10͞56 (29) and 18͞176 (39)]. Second, previous studies show that genetic groups distinguished by this 1-kb probe agree with genetic groups identified by much longer probes (26 kb) and multi-locus enzyme electrophoresis analysis (39,49). Therefore, we are confident that the major chromosomal types distinguished with the 1-kb probe are genetically different groups within this population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is therefore not surprising that our relatively short chromosomal probe detected a similar number of genetic groups per isolate sampled as was found in previous studies [8 genetic groups͞69 isolates sampled in this study compared with 10͞56 (29) and 18͞176 (39)]. Second, previous studies show that genetic groups distinguished by this 1-kb probe agree with genetic groups identified by much longer probes (26 kb) and multi-locus enzyme electrophoresis analysis (39,49). Therefore, we are confident that the major chromosomal types distinguished with the 1-kb probe are genetically different groups within this population.…”
Section: Discussionsupporting
confidence: 87%
“…The occurrence of traits on plasmids may generally elevate genetic diversity and rates of evolution because of higher mutation rates or increased levels of reiterated DNA (5). Previous studies detecting a greater number of distinct genetic groups at sym than chromosomal loci suggest higher diversity at nod loci, with up to five distinct sym types per chromosomal group (31,39,49). This increased variability in the sym genome has been attributed to recombination within the sym plasmid, facilitated by the high frequency of reiterated sequences around the sym plasmid (18,25,31).…”
Section: Discussionmentioning
confidence: 96%
“…The species of legume cultivated can also markedly affect the nature of the soil population. While most of the studies mentioned above have reported a clonal population structure, a number suggest the possibility of recombination between particular groups of soil rhizobia (Demezas et al, 1995;Sullivan et al, 1995) and both plasmid transfer between strains (Jarvis et ai., 1989;Kinkle and Schmidt, 1990;Thomas et al, 1994;Young and Wexler, 1988) and chromosomal symbiotic gene transfer (Sullivan et al, 1995) have been noted.…”
Section: N Soil Populations Of the Rhizobia And Their Diversitymentioning
confidence: 96%
“…This evidence included a poorly resolved consensus tree of gene phylogenies with many homoplasies, as well as the absence of association between alleles at different loci in tests of linkage disequilibrium (Burt et al, 1996). Evidence of recombination has also been observed in natural populations of several bacteria and parasitic protozoa that had been assumed to be mainly clonal (Maynard Smith et al, 1993;Istock et al, 1992;Souza et al, 1992;Demezas et al, 1995).…”
mentioning
confidence: 95%